ISLAMIC EDUCATION AT MTSN 1 TAPANULI TENGAH IN THE COVID 19 ERA - Munawir Pasaribu; Rahman Rizki Tanjung (Proceeding International Seminar of Islamic Studies, 2021)
Coronavirus is an unexpected plague that can be said to be a health crisis.Social distensing is critical to breaking the chain of covid 19,Thus, it affects the education world without exception in MTSN 1 Tapanuli Tengah but it also applies online learning through electronic media, even though the signal in barus is fine but the problem is the inability of parents to buy gadgets from their children, so many inactive students learn through this method. The purpose of this writing is to know the impact of islamic education in MTSN 1 Tapanuli Tengah during the pandemic of covid 19 research subjects of this writing also includes teachers and students MTSN 1 Tapanuli Tengah The method is a qualitative method in the form of case studies.Keywords : covid 19,Influence of Islamic education